Impact of School-Based Oral Health Education on Vietnamese Adolescents: A 6-Month Study - Nguyen, Vy Thi Nhat (Int J Environ Res Public Health, 2021)
We have evaluated the impact of a school-based intervention on oral health knowledge, behaviours, and oral health status of adolescents in Vietnam. This 6-month study included 462 adolescents aged 12 years from four selected schools in Hue City, Vietnam. The intervention group received a 15-min lecture by a dentist and hands-on session on mouth observation and toothbrushing skills. The control group did not engage in any educational activities during the follow-up period. Data were collected at baseline and 6 months through a survey questionnaire and clinical examination. The Debris Index was used for dental plaque; the Papillary, Marginal, Attached gingiva index for gingivitis; and the Decayed, Missing, and Filled Teeth index (World Health Organization modification) for dental caries. Difference-in-difference analysis was used to compare changes between the groups. After 6 months, the control tended to show decreased toothbrushing frequency and increased dental plaque accumulation. The participants in the intervention group showed improved oral health knowledge (p < 0.01), behavior (p < 0.05), and hygiene (p < 0.001) compared to the control group. However, the intervention did not improve dental caries and gingivitis. A single school-based oral health education program can help adolescents improve oral health knowledge and prevent the deterioration of short-term oral health behavior and hygiene.